Barriers to implementing health programs based on community participation: the Q method derived perspectives of healthcare professional - Hassan Mahmoodi; Amjad Mohamadi Bolbanabad; Abdolreza Shaghaghi; Mehdi Zokaie; Reza Ghanei Gheshlagh; Abdorrahim Afkhamzadeh (BMC, 2023)
Abstract Background Community participation in implementing health programs leads to positive organizational, social and individual consequences. This study aimed to investigate the prospects of a sample of Iranian healthcare professionals about their perceived barriers to implementing health programs based on community participation. Methods This was a cross-sectional study that employed a Q-methodology approach. Twenty health professional sorted the 47 statements into a 9-column Q-sort diagram ranging from − 4 as not important to + 4 as very important. The data were analyzed with PQMethod 2.35 software. The centroid factor analysis and varimax rotation were used for data analysis. Factors identified were interpreted and described in terms of the participants perspectives on the phenomenon. Results Analysis of the study participants' viewpoints (the Q-sorts) resulted in a five factor solution (accounted for 57% of the total variance) to endorse the main barriers to the implementation of health programs based on community participation in Iran. Barriers related to government, health programs, lack of necessary skills amongst health professionals and weak coordination between departments, barriers related to community, lack of understanding of goals, benefits and transparency of roles and responsibilities were among the important emanated factors to implementing health programs based community participation. Conclusion Health policymakers and managers should consider the five mentioned identified barriers based on the community when planning and implementing the health program participation and try to empower the community to implement the programs in Iran.